THE CATHOLICISM MEDIATIZATION IN THE ASPECT OF THE CHURCH INFORMATION DEPARTMENTS ACTIVITY - Филипчук, С. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
The aim of the article is to outline the process of the Catholicism mediatization through the directions analysis of the information de-partments of the RCC in Ukraine and the UGCC activities. Research methods: The presented research is based on the use of interdis-ciplinary approaches, such as philosophical, communicative, religious studies, to clarify the essence of the religion mediaization pro-cess. Discussion. In this article we rely on the concept of religion mediatization, which was developed by the Danish scientist S. Hjarvard, affirming that in a society saturated with media, religion can not exist outside the media space and undergoes significant trans-formations under the influence of mass media. Conclusions. The process of the Catholicism mediatization is being traced in the Ukrainian public space, which is publicized through the prism of multi-vectoral activities of the information structures of the RCC and the UGCC. Such structures in a secularized environment act as generators of the discourse between churches, believers and new believ-ers. Informational structures are mostly engaged in a variety of extracult activities, which, through social communications, articulate the important issues for the Catholic people in the social-religious discourse. Working mostly on the profane territory, these organizations bring sacred meaning to the secular media environment. The process of the Catholicism mediatization in the measure of activities of the information structures is characterized by the incorporation through secular and confessional mass media into all spheres of life of Ukrainian society. Thus, the mediaization of Catholicism in Ukraine deepens the processes of politicization of religion, the sacralization of politics, the consumerism, the privatization of religion and secularization that are present in Ukrainian society.